Joint complaints frequency and rheumatoid arthritis prevalence in Republic of Ingushetia - S F Erdes; D I Basorkina (Научно-практическая ревматология)
Objective. To study joint complaints frequency and rheumatoid arthritis (RA) prevalence among republic of Ingushetia residents. Material and methods. Questionnaire study of a random population ofNasran city residents (4000 people) and general questionnaire study of several refugee temporary settlements (2000 people) with subsequent examination of all 270 people having joint swelling during the last year. Results. Knee and/or hip joint pain frequency among Ingushetia residents is 27,6%. It increases with age and reaches 100% among people older than 70 years. About 12% of people had history of joint swelling during the last year or earlier, 2% had joint swelling during the last year. Prevalence of RA among Ingushetia residents is 0,56% Conclusion.